Archaeological Heritage in Early childhood and Primary education: An approach to future teachers’ interests and difficulties - López-Mondéjar, Leticia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In recent years, diverse proposals have highlighted the interest in working with archaeological heritage in the classroom, starting from the Early Childhood educa- tion. However, few experiences have addressed key issues in connection with it, such as teacher training on the subject and its educational uses, the didactic interest given by teachers to it and the difficulties they find in implementing proposals in this field. The objective of this study is to approach these issues paying attention to the vision that future teachers of Early Childhood and Primary education have about them.